Youth, Identity, and Digital Media - Buckingham, David (The MIT Press, 2007)
Contributors discuss how growing up in a world saturated with digital media affects the development of young people's individual and social identities.As young people today grow up in a world saturated with digital media, how does it affect their sense of self and others? As they define and redefine their identities through engagements with technology, what are the implications for their experiences as learners, citizens, consumers, and family and community members? This addresses the consequences of digital media use for young people's individual and social identities. The contributors explore how young people use digital media to share ideas and creativity and to participate in networks that are small and large, local and global, intimate and anonymous. They look at the emergence of new genres and forms, from SMS and instant messaging to home pages, blogs, and social networking sites. They discuss such topics as "girl power" online, the generational digital divide, young people and mobile communication, and the appeal of the "digital publics" of MySpace, considering whether these media offer young people genuinely new forms of engagement, interaction, and communication.ContributorsAngela Booker, danah boyd, Kirsten Drotner, Shelley Goldman, Susan C. Herring, Meghan McDermott, Claudia Mitchell, Gitte Stald, Susannah Stern, Sandra Weber, Rebekah Willett